Quantitative determination of unbound levofloxacin by simultaneous microdialysis in rat pancreas after intravenous and oral doses. (24th June 2014) - Liu, Deding; Xu, Shuogui; Xiao, Heping; Wang, Zhuo; Mao, Ningfang; Zhou, Jia; Liu, Rui; Huang, Yi
Abstract Objective We compared the pharmacokinetic profile of unbound levofloxacin in rat pancreas after an oral dose with that after an intravenous dose to determine if oral administration of levofloxacin could potentially be used. Method Levofloxacin was administered either intravenously or orally into male Sprague‐Dawley rats at the concentration of 42 mg/kg per day, mimicking the human dose of 400 mg/day. The concentrations of levofloxacin in extracellular fluid (ECF) of rat pancreatic tissues were determined using microdialysis coupled with high‐performance liquid chromatography (HPLC). Levofloxacin was equally distributed into ECF of rat pancreatic tissues with either intravenous route (AUCpancreas/AUCblood, 0.97 ± 0.02) or oral route (AUCpancreas/AUCblood, 0.96 ± 0.03). Key findings The penetration rates (PR) of pancreas‐to‐blood on the same target site between the two routes were the same. The intravenous antibiotic AUC/MIC ratios of common Gram‐positive pancreatic bacteria ranged from 83.43 to 667.44; meanwhile, the ratio of common Gram‐negative pancreatic bacteria ranged from 41.71 to 2669.74. The oral antibiotic AUC/MIC ratios for common gram‐positive and Gram‐negative pancreatic bacteria were from 78.54 to 628.31, and 39.27 to 2513.22, respectively (P > 0.05). Conclusions Intravenous administration had similar penetration efficacy to oral administration at an equivalent dose. Furthermore, levofloxacin had a good penetration through the blood–pancreas barrier.